El concepto de la agresión en el Derecho Internacional Público y su influencia en el derecho doméstico argentino. Debates sobre su pertinencia y limitaciones - Rial, Juan Alberto (International Relations, 2018)
The concept of agression has been very important in International Law. International Law has used the concept of aggression as a central notion when it was the moment to legislate and to start working on institutions linked to the maintenance of international peace a security. The same happed with the Collective Security Architecture. When the National Defense Law (23.544) was regulated why the decree 727/06 the concept of aggression adopted by the United Nations was transfer without baring in mind the complements with which the concept becomes a hole in the context of that organization. The new decree 683/18 solved that problem but not without controversy.